2021
DOI: 10.1177/0739532921989490
|View full text |Cite
|
Sign up to set email alerts
|

Representations of refugees in their home countries and abroad: A content analysis ofla caravana migrante/the migrant caravan in Central America and the United States

Abstract: In October 2018, Honduran citizens started walking toward the American South border looking to be allowed entry into the United States due to not having work opportunities nor humanitarian aid in Honduras. More people joined them and this group was named la caravana migrante, the migrant caravan. Our content analyses of articles in five U.S. and five Central American newspapers sought to find similarities and differences in reporting. Despite differences in language and proximity to the caravan, reporting show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
2
0
2
Order By: Relevance
“…These geopolitical differences in coverage can also be due to the proximity of an issue. For example, CA newspapers were more likely to present a human interest frame if they had close proximity to migrant caravans, and an economic frame if they had more distance (Kenix & Lopez, 2021). However, other research has found that the closer refugees are in proximity, the more negative the consequences (Parrott et al, 2019).…”
Section: Global Media Frames and Journalism Normsmentioning
confidence: 97%
See 1 more Smart Citation
“…These geopolitical differences in coverage can also be due to the proximity of an issue. For example, CA newspapers were more likely to present a human interest frame if they had close proximity to migrant caravans, and an economic frame if they had more distance (Kenix & Lopez, 2021). However, other research has found that the closer refugees are in proximity, the more negative the consequences (Parrott et al, 2019).…”
Section: Global Media Frames and Journalism Normsmentioning
confidence: 97%
“…The strong relationship between media framing and political power in global societies (Entman, 2003) strongly suggests that how an individual or group is framed in the media has "real world" effects (McCombs, 2020). Thus, media can shape how refugees interpret their home country; how those in their home country and new country view their migration to the US (Liu, 2023;Parrott et al, 2019); how refugees are viewed when they arrive (Kenix & Lopez, 2021;Llewellyn et al, 2021); and resultant policies toward refugees and migrants (Chattopadhyay, 2019). This research explores how news media in six different countries throughout CA, Mexico, and the US portrayed refugees through a continued period of interlocking crises from 2012-2022: political instability, repression, natural disasters, climate change, gang conflicts, and economic collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, la cobertura de los acontecimientos trágicos, como las crisis migratorias, se realiza desde una perspectiva más humana retratando a los inmigrantes como víctimas, cuyos derechos deben ser respetados (Ustad & Thorbjørnsrud, 2015;Greenwood & Thomson, 2019). Se destaca la ausencia o la escasa presencia de las voces de los propios inmigrantes, particularmente en las noticias de la prensa estadounidense (Thorbjørnsrud & Ustad, 2014), tendencia observada también en la cobertura de la caravana migrante de 2018 (Kenix & Bolanos, 2021). Este fenómeno contrasta con los resultados del estudio de la cobertura de la caravana en los diarios mexicanos, donde se apela a los testimonios de los inmigrantes (Portales & Miranda, 2021).…”
Section: Marco Teórico: Encuadres Sobre La Inmigraciónunclassified
“…Los resultados del análisis contrastan la abundancia de los testimonios de los inmigrantes en el periódico mexicano en comparación con el estadounidense, una característica destacada por los estudios previos de la cobertura de la caravana migrante que señalan la presencia de la voz de los inmigrantes en la prensa regional mexicana (Portales & Miranda, 2021) y su insuficiencia en los periódicos estadounidenses (Kenix & Bolanos, 2021). La Jornada muestra a los inmigrantes en una di-mensión humana poniendo acento en el hecho de que son personas vulnerables que experimentaron dramas y tragedias en sus vidas y que huyen de la violencia buscando un mejor futuro.…”
Section: Conclusionesunclassified